PENINGKATKAN KEPUTUSAN BERKUNJUNG MELALUI E-WOM, FASILITAS DAN CITRA DI DESTINASI WISATA EDUKASI - Fahimah, Mar'atul; Mubariroh, Syarifatul (JURNAL DIMENSI, 2025)
Kandang Sapi Wonosalam is one of the educational and play tourism destinations with a modern packaged livestock concept. This study aims to identify whether there is an influence that occurs between E-WOM, facilities and destination image on the decision to visit the Kandang Sapi Wonosalam Jombang. This study uses an associative method with a quantitative approach. The population in this study is all tourists who visit Kansa Wonosalam tourism and tourists who read comments on Kansa Wonosalam Instagram posts. To obtain data that is in accordance with this study, the researcher uses a quantitative approach and questionnaire as a medium in collecting data and uses purposive sampling techniques in determining respondents. The total respondents in this study were 100 respondents. This study uses multiple linear regression analysis technique with the data used, namely validity and reliability tests, multiple linear regression analysis tests, classical assumption tests, and hypothesis tests (t-test) and determination coefficient tests (R2). Based on the test results, it was said that the E-WOM variable (X1) was declared to have no significant influence of E-WOM on the decision to visit (Y) to Kansa Wonosalam Tourism. Meanwhile, the facility variable (X2) was stated that facilities had a positive and significant effect on the decision to visit (Y) to Kansa Wonosalam Tourism. And the destination image variable (X3) was stated that there was no significant influence of destination image on the decision to visit (Y) to Kansa Wonosalam Tourism